Data in Schools: (Changing) Practices and Blind Spots at a Glance - Krein, Ulrike; Schiefner-Rohs, Mandy (Frontiers in Education, 2021)
This review aims to provide a concise overview of the role of (digital) data and emerging data prac-tices in schools. By focusing on the influence of data on pedagogical practices, it will shed light on how the everyday tasks of teachers and other pedagogical staff in schools are changing as a result of the generation and use of digital data in particular. For this purpose, existing studies and previous theoretical debates on this topic are examined based on their perspectives on data, data practices, and education in schools. The pedagogical data practices of (improving) teaching and learning, as-sessing and counseling, as well as decision-making will be elaborated and discussed. Likewise, data practices that are lacking in the studies are identified. We conclude with an overview of blind spots and further research needs.